The Effects of Vitamin E Administration in Non-Alcoholic Fatty Liver Disease - Handayani, Tri; Prijanti, Ani Retno (HM Publisher, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a liver disease which has high prevalence in the society. There is no drug that is considered to be able to effectively treat this disease until today. The treatments has wide range from modifications to diet and exercise. The role of vitamin E in the treatment of NAFLD has been studied in many researches. It has high antioxidant capacity that have the ability to decrease the level of reactive oxygen species (ROS) and prevent oxidative damage that can cause cellular senescence and apoptosis. The antioxidant properties may inhibit the progression into liver damage and may even treat hepatic fibrosis in NAFLD. It also has an anti-inflammatory role that affects various inflammatory cytokines produced in NAFLD. The use of vitamin E in non-alcoholic steatohepatitis without diabetes is advised by recent guidelines from the American Association for Study of Liver Disease (AASLD) and the European Association for the Study of Liver Disease (EASLD). In patients with non-alcoholic steatohepatitis, vitamin E can decrease oxidative stress, inhibit the pathogenesis of the disease, and be used as a therapeutic option. However, new research on the safety and efficacy of vitamin E in treating diabetic non-alcoholic steatohepatitis patients is still deemed insufficient.